2018
DOI: 10.1016/j.jvs.2018.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of anatomic indications for the Nellix System for endovascular aneurysm sealing based on 2-year outcomes from the EVAS FORWARD IDE trial

Abstract: Consistent with the introduction of a novel therapy, the presentation of failure modes of EVAS over time was inevitable. Using detailed imaging as well as engineering and statistical analysis, we were able to understand risk factors for adverse events specific to EVAS and defined those patients best suited for Nellix. With this EVAS-specific approach to defining IFU, on-IFU patients were identified as those with large aneurysms with little thrombus that would be prone to type II endoleaks and sac expansion wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 13 publications
1
41
2
Order By: Relevance
“…12,[14][15][16] In 2016, EVAS FORWARD, an investigational device exemption trial, reported higher than expected rates of distal migration, type IA endoleak, and aneurysm sac expansion, leading to a refinement of the instructions for use (IFU). 17 The revised IFU addressed the proximal and distal seal zones and thrombus burden within the aneurysm, with a view to reducing device migration (Supplementary Table I, online only). The new IFU suggested that EVAS would be most effective and durable in large AAA with little thrombus and neck criteria similar to the IFU for other commercially available endovascular aneurysm repair (EVAR) stent grafts.…”
mentioning
confidence: 99%
“…12,[14][15][16] In 2016, EVAS FORWARD, an investigational device exemption trial, reported higher than expected rates of distal migration, type IA endoleak, and aneurysm sac expansion, leading to a refinement of the instructions for use (IFU). 17 The revised IFU addressed the proximal and distal seal zones and thrombus burden within the aneurysm, with a view to reducing device migration (Supplementary Table I, online only). The new IFU suggested that EVAS would be most effective and durable in large AAA with little thrombus and neck criteria similar to the IFU for other commercially available endovascular aneurysm repair (EVAR) stent grafts.…”
mentioning
confidence: 99%
“…102,121 The risk of sac rapture has greatly diminished with new-generation endografts but remains a nonnegligible risk for young patients with long life expectancy ( Figure 8). 14,59,60,118,[122][123][124] This underscores the importance of surveillance post EVAR and prompt intervention for sac growth >5 mm or a persistent endoleak. 117,121 5.6 | Evidence supporting access site closure after EVAR Percutaneous femoral access for EVAR has increased compared to surgical cutdown.…”
Section: Guidelines For Aaa Surveillancementioning
confidence: 97%
“…The distal aortic body with the iliac limb is deployed first, followed by the proximal aortic body (Figure d,e). Polymer sealing design: For this low‐profile design, the aortic body is deployed first, a polymer is injected to create an aortic neck seal, the contralateral aortic limb gate is cannulated, and then the iliac limbs are deployed sequentially. Future devices in which a polymer is employed to fill and actively manage the AAA sac are still under clinical investigation (Figure f) …”
Section: Endovascular Aneurysm Repair Techniquesmentioning
confidence: 99%
See 2 more Smart Citations